Integrasi Progressive Web App dan Sistem Informasi Geografis untuk Penyediaan Informasi Lokasi dan Harga Penyewaan Gendang Beleq di Lombok - Baiq Andriska Candra Permana; Zaenul Amri; Gunawan Rohadi; Zulkipli (Fakultas Teknik Universitas Hamzanwadi, 2026)
Gendang Beleq is a traditional musical art of the Sasak people that continues to be preserved in Lombok. However, the process of renting Gendang Beleq instruments in East Lombok is still done manually, which makes it difficult for people to access clear and reliable information about rental locations, prices, and provider contacts. This study aims to develop a Progressive Web App (PWA)-based Geographic Information System that can provide accurate, fast, and easy-to-access information related to Gendang Beleq rentals. The research uses a Research and Development (R&D) approach with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The developed system displays an interactive map showing the locations of rental providers along with complete details such as prices, contacts, and descriptions of the instruments. The system also supports key PWA features, including app installation and offline access. Performance testing using GTMetrix resulted in scores of 98% for the admin application and 97% for the user application. Functional testing showed that the system is highly feasible, with alpha testing results of 94.5% for the admin system and 100% for the user interface, while beta testing achieved a 98% feasibility score. Overall, the PWA-based GIS developed in this study is considered effective, user-friendly, and capable of supporting the availability of Gendang Beleq rental information in East Lombok.